Extracorporeal Cardiopulmonary Resuscitation for Management of Out-of-Hospital Cardiac Arrest in a Patient with Fulminant Myocarditis - Alexander J. Meyer; Michael A. Biersmith; Ernest L. Mazzaferri; Konstantinos Dean Boudoulas (Case Reports in Critical Care)
A 68-year-old male with a witnessed out-of-hospital cardiac arrest while jogging who was managed with extracorporeal cardiopulmonary resuscitation (ECPR) is presented. The patient was found to be in refractory ventricular fibrillation by emergency medical service personnel and underwent advanced cardiac life support (ACLS) protocol with placement of an automated chest compression device. He was emergently transported to the cardiac catheterization laboratory. Due to refractory ventricular fibrillation, he was placed on venoarterial extracorporeal membranous oxygenation (VA-ECMO). Coronary angiography at that time showed nonobstructive coronary artery disease. Management with VA-ECMO and other supportive measures were continued for 5 days, after which a cardiac magnetic resonance imaging was performed with findings consistent with acute myocarditis. His condition substantially improved, and he was discharged from the hospital with good neurologic and functional status. Fulminant myocarditis is often fatal, but aggressive supportive measures with novel ECPR protocols may result in recovery, as it happened in this case.